The "Marry to Work" Approach: Understanding the Mechanisms of Marriage of Convenience amongst Syrian Refugee Women in Egypt - Badr, Doha (AUC Knowledge Fountain, 2021)
Transnational marriage of convenience in refugee context is a unique perspective to reflect the livelihoods reality of Syrian female refugees in Egypt as a host country. Transnational marriage of convenience is a gateway for many Syrian female refugees to be legally integrated and socioeconomically incorporated in Egypt, setting challenging conditions for refugees to attain a work permit. This paper employs the bargaining power model to uncover how different legal regimes contribute to shaping the dynamics of the transnational marriage of convenience. The paper argues that the position of Syrian female refugees in the Egyptian labor market is closely linked to the intersection between four main legal regimes: Egyptian family law, nationality law, Egyptian labor law, and international refugee law. This intersection determines the bargaining power structure in a transnational household in the refugee setting. The bargaining power model explains how Syrian female refugees adopt an opportunistic behavior to retain the restricted right to work where they take advantage of the fruits of intersection between two different legal regimes, which are the Egyptian nationality law and family law, to overcome the negative implications of the intersection between the Egyptian labor laws and the international refugee law. The operational way to achieve this gain is to get involved in transnational legal marriages of convenience more progressively.